Supporting Refugee Women and Children During Armed Conflict. Issue 5 (September 2022) - Callister, Lynn Clark
Abstract : The armed conflict in Ukraine has caused millions of refugees, mostly women and children. Our global health and nursing expert, Dr. Callister, who has lived and worked in Kyiv, Ukraine, covers this crisis and what it means for the health and safety of refuges fleeing a country at war.